PENGEMBANGAN PEMBELAJARAN MENULIS CERPEN DENGAN MENGGUNAKAN MODEL SINEKTIKA SISWA KELAS XI SMK NEGERI 2 SAMARINDA - Herniwati Rahmat Soe’oed Akhmad Murta (Kantor Bahasa Kalimantan Timur, 2018)
This research aims (1) to know the development process in the learning of short story writing, (2) to measure the validity and practicality of short story writing using synectics learning model, and (3) to measure the effectiveness of short story writing using synectics learning model. It uses a Research and Development (R&D) model of Borg and Gall. The population of this research is 30 students of class XI SMK Negeri 2 Samarinda. Trials were conducted in two stages, small group and large group or field trials. Methods of data collection include observation, interview, and test. It applies descriptive and qualitative techniques to analyze the data.